2015
DOI: 10.3892/ol.2015.3667
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin G2: A novel independent prognostic marker in pancreatic cancer

Abstract: Abstract. Unlike other cyclins that positively regulate the cell cycle, cyclin G2 (CCNG2) regulates cell proliferation as a tumor suppressor gene. A decreased CCNG2 expression serves as a marker for poor prognosis in several types of cancer. The aim of the present study was to clarify the correlation of CCNG2 expression with overall survival and histopathological factors in pancreatic cancer patients. This retrospective analysis included data from 36 consecutive patients who underwent complete surgical resecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 23 publications
(41 reference statements)
1
13
1
Order By: Relevance
“…While ALDH1A1 and MYC genes were reported in metastasis of several tumor types and associated with poor prognosis [ 39 , 45 , 47 , 62 , 63 ], for CCNG2, a cell cycle checkpoint cyclin upregulated in response to DNA damage, the association to stemness was not clear. It was reported to have tumor suppressor functions in different neoplasias [ 64 , 65 ], although, supporting our observations, CCNG2 positively associated with prostate cancer recurrence after radical prostatectomy [ 46 ]. CCNG2 induces microtubule bundling and stability, and contributes to resistance to chemotherapy, presumably by facilitating a delay in the transition from G1/S to G2/M phase that allow reorganization of microtubules and chromatin repairs after drug exposure [ 34 , 66 68 ].…”
Section: Discussionsupporting
confidence: 84%
“…While ALDH1A1 and MYC genes were reported in metastasis of several tumor types and associated with poor prognosis [ 39 , 45 , 47 , 62 , 63 ], for CCNG2, a cell cycle checkpoint cyclin upregulated in response to DNA damage, the association to stemness was not clear. It was reported to have tumor suppressor functions in different neoplasias [ 64 , 65 ], although, supporting our observations, CCNG2 positively associated with prostate cancer recurrence after radical prostatectomy [ 46 ]. CCNG2 induces microtubule bundling and stability, and contributes to resistance to chemotherapy, presumably by facilitating a delay in the transition from G1/S to G2/M phase that allow reorganization of microtubules and chromatin repairs after drug exposure [ 34 , 66 68 ].…”
Section: Discussionsupporting
confidence: 84%
“…The current literature suggests that CCNG2 plays an important inhibitory role in cancer initiation and progression [60]. It has been shown that CCNG2 dysregulation is related to cancer progression and could play an important role in cell transformation and the early stages of cancer development [60,61]. Seemingly, our findings would seem to contrast with the role played by CCNG2 in cancer.…”
Section: Discussioncontrasting
confidence: 72%
“…Unlike other cyclins, the expression of cyclin G2 increases in cycle‐arrested and terminally differentiated cells . A large body of evidence indicates that cyclin G2 acts as an important tumour suppressor . Recent findings have suggested that the expression of cyclin G2 in fatty tissues of obese patients is associated with steady‐state of carbohydrate metabolism in the body .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 A large body of evidence indicates that cyclin G2 acts as an important tumour suppressor. [3][4][5][6] Recent findings have suggested that the expression of cyclin G2 in fatty tissues of obese patients is associated with steady-state of carbohydrate metabolism in the body. 7 Furthermore, in patients with type 2 diabetes, the level of cyclin G2 is positively correlated with that of insulin-degrading enzyme (IDE).…”
Section: Introductionmentioning
confidence: 99%